Foreign Students’ Perception on Online Graduate Education in a Philippine University - Cuello, Freshtille Mae (JPAIR Institutional Research, 2019)
Online education is an academic offering being eyed by universities as a lucrative venture.  The offering of virtual courses allows institutions to intensify international competitiveness and presence. Most universities are determined to attract and reach the global student populace to stay ahead and secure their mark as game-changers in a contemporary academic race and make available online courses for foreign graduate students to experience independent intellectual development and professional advancement. It is the primary aim of this study to present the profile of foreign students of a Philippine university. Moreover, a data mine is also provided to preview their shared perception on a preferred instructional model for education from the following: traditional, virtual, or blended. The descriptive research method was employed in the study. The Likert Scale was also used to measure the attitude and strength of the self-assessment of the respondents. The foreign students were at the crossroads of embracing traditional education and virtual or online education for graduate courses. They perceived that traditional education gave the benefit of more personal communication between peers and professors, while online education delivered convenience and flexibility. These opportunities are in no way found in one method alone. Moreover, course offerings, the reputation of the university, and fewer class meetings are factors foreign students consider for online courses.
Keywords: Technology-based instruction; virtual or online courses; descriptive method; Philippines